Perancangan Inkubator Otomatis Berbasis Arduino - Putranto, Hudaifa Aga Putranto; Desriyanti, Desriyanti; Intan Vidyastari, Rhesma (FORTEI Regional VII Jawa Timur, 2025)
Abstract - Baby care is crucial from the moment a newborn arrives. During this early stage, brain and body development are the main focus, especially for babies born prematurely or with low birth weight. Parents and close caregivers must always provide careful supervision and the best care until the baby reaches one year old.This study resulted in the development of a Baby Incubator designed to monitor and regulate the baby’s temperature, weight, and heart rate continuously. The incubator uses an LM35 sensor to measure temperature, a load cell to measure weight, and a heart pulse sensor to track the baby’s heartbeat. All the data is displayed on a graphical LCD screen, enabling parents and caregivers to keep a close watch on the baby’s condition. The incubator was tested on four babies of different ages and genders to ensure accuracy and reliability. The device container measures 70 cm by 40 cm, with a height of 30 cm, and is powered by a 12V power supply that runs all sensors, the LCD, and a buzzer for alerts. When compared with equipment at RSI Siti Aisyah Madiun hospital, the incubator showed accurate weight and temperature measurements. The heart rate sensor’s accuracy was approximately ±96% compared to the hospital’s tools. These readings help doctors and midwives monitor premature babies effectively and make informed decisions about their care